Micropropagation of Isoplexis chalcantha Svent, O´Shanahan from Mature Plants - Mederos-Molina, S. (Plant Tissue Culture and Biotechnology, 2009)
Culture medium requirements for micropropagation of Isoplexis chalcantha was achieved for the first time after high degree of contamination and phenolic exudates were detected and solved. Cultures were established from axillary shoots using juvenile branches collected from this medicinal plant. Most satisfying results were obtained using a solidified and a modified MS medium (NO3- : NH4+ ratios) enriched with ascorbic acid or soluble PVP plus GA3, BAP and NAA. Explants (nodal segments) were used for in vitro shoots multiplication and best results were achieved with modified MS plus BAP and auxins. Vigorous shoots rooted without symptoms in the half-strength modified MS enriched with low concentration of IBA. Key words: Isoplexis chalcantha, axillary shoots, contamination, phenolic exudates, culture media, NO3- : NH4+ ratios D.O.I. 10.3329/ptcb.v18i2.3395 Plant Tissue Cult. & Biotech. 18(2): 131-137, 2008 (December)